New Synthesized Galloyl‐RGD Inhibits Melanogenesis by Regulating the CREB and ERK Signaling Pathway in B16F10 Melanoma Cells. (10th August 2020) - Shin, Seo Yeon; Sun, Sang Ouk; Ko, Jae Yeon; Oh, Yun Seo; Cho, Seung‐Sik; Park, Dae‐Hun; Park, Kyung Mok
Abstract: Gallic acid (3, 4, 5‐trihydroxybenzoic acid) is a phytochemical derived from diverse herbs. It has been reported to have effective antifungal, antiviral and antioxidant activity. However, gallic acid exhibits low solubility and instability at high temperatures. In a previous study, in order to overcome these limitations, we synthesized galloyl‐RGD by combining gallic acid with arginine, glycine and asparaginic acid (RGD peptide). This compound showed better thermal stability than gallic acid. In this study, we investigated the antimelanogenic effect of galloyl‐RGD and the underlying mechanism for this effect. Galloyl‐RGD markedly inhibited melanin content and tyrosinase activity in a concentration‐dependent manner. We also found that galloyl‐RGD decreased the levels of melanogenesis‐related gene and protein. In addition, galloyl‐RGD reduces intracellular cyclic adenosine monophosphate (cAMP) levels that leads to inhibition of cAMP‐responsive element binding protein (CREB) phosphorylation and activates extracellular signal‐regulated kinase (ERK) expression. These results indicate that CREB and ERK regulation by galloyl‐RGD contributes to reduced melanin synthesis via degradation of microphthalmia‐associated transcription factor. Therefore, galloyl‐RGD can be potential candidate for application in cosmetic or pharmaceutical industry. Abstract : Galloyl‐RGD is a combination of gallic acid and RGD peptides (arginine, glycine and asparaginic acid). In this study, galloyl‐RGD indicates that CREB and ERK regulation contribute to reduced melanin synthesis through degradation of microphthalmia‐related transcription factor.